Mezinárodní migrace v České republice - Knězáčková, Radka; Volejníková, Jolana (Univerzita Pardubice, 2015)
The interregional migration in the Czech Republic is not so massive in comparison with other states (the USA, Germany). The Czech citizens are not used to migrate for work. But we can notice that the number of moved people has been increasing in the last ten years. It is also caused by the increasing differences between regions. The aim of the article is determined whether interregional migration in the Czech Republic is related with the economic level of the region. Although the decision to move is the individual decision of each person, it is influence by phenomena from economic, social and cultural life and they affect the final decision. The article deals with the determinants of interregional migration in the Czech Republic. It is based on the findings of migration theories that were formed during 20th century. It defines the main causes of human migration and examines their impact in the Czech Republic.
Migration between regions in the Czech Republic
Keywords: determinants of migration; interregional migration; theories of migration; O15; R23